Kajian Manajemen Energi Listrik Pada Stasiun Pompa Air - Mohammad Noor Hidayat; Sigi Syah Wibowo; Moch. Guntur Eka Prasetya (Politeknik Negeri Malang, 2020)
To operate the water pump, an electric motor is needed as the driving force. In order for the energy consumption needed to operate an electric motor to be regulated, it is necessary to manage electrical energy at the pump station. One example of a pump station is the local water company (PDAM) Unit Wendit Malang City. This unit consists of 3 pump stations namely Wendit 1, Wendit 2 and Wendit 3. These three parts are supplied by 2 transformers with a capacity of 1110 kVA for Wendit 2 and 1730 kVA for Wendit 1 and 3.From the results of power factor measurements in the three sections, it is known that the power factor value at the Wendit 3 pump station is 0.82. This value does not meet the PLN minimum standard, which is 0.85. To improve the low power factor, two recommendations were given, namely the installation of VSD (Variable Speed Drive) at the PDAM Unit Wendit 1 and 3 pump stations and the installation of a Capasitor Bank at the PDAM Unit Wendit 2 pump station.Based on the analysis, the power factor value PDAM Wendit 3, which was originally 0.82 increased to 0.9. In addition, there are savings in electricity consumption per month of 10.48% at PDAM Unit Wendit 1 and 3 and 28.32% at PDAM Unit Wendit 2.